Administração pública e diretrizes curriculares da educação ambiental: processos de ambientalização na Universidade Federal de Sergipe - Oliveira, Susana Maria Andrade (2022)
The research aimed to survey the practices of the Federal University of Sergipe (UFS) in the sense of promoting sustainable development and the inclusion of environmental issues in the curriculum. The objects of study are the administration and the academic areas, involving teaching, research, and extension. To identify the administrative and educational actions developed by UFS towards environmental issues and the impacts promoted by these actions in the academic community, we seeked to: (a) evaluate the process of incorporating the A3P (Environmental Agenda in Public Administration) concepts and guidelines in the administrative management of UFS; (b) identify how environmental issues are being inserted in the curricula of undergraduate courses; (c) Identify which research and extension actions addressed environmental issues; (d) evaluate the gaps in the environmentalization processes at UFS, its causes and consequences. For the research, the Structuralist Method was used, being developed, fundamentally, as an exploratory and explanatory research following a quantiqualitative approach, using bibliographic and documentary research as techniques. The bibliographic research was don ethrough the analysis of books, scientific publications, and journal articles that allowed a better conceptual definition of the object of study. Regarding the documentary research, official documents from UFS were examinedthat supported an analysis of the chronology and methods used in the institution's environmentalization processes, in the period from 2010 to 2020. The research identifiedadministrative and educational actions developed by UFS in the sense of environmentalization processes,analyzing the impacts promoted by these actions in the academic community, enabling possible comparisons and transfers (not generalizations) to other contexts.